Digital optical archiving of medical records in hospital information systems: a practical approach towards the computer-based patient record? - Dujat, Carl; Haux, Reinhold; Schmücker, Paul; Winter, Alfred (Methods of information in medicine, 1995)
The large number of inpatients and outpatients in university hospitals leads to high costs of medical documentation and to an increasing number of medical documents. Due to legal regulations, these medical records have to be stored for 30 years. This implies spatial, organizational, and economical problems. At present, conventional archiving in hospitals often does not satisfy the need to make medical records available for healthcare professionals in a systematic and timely manner. From 1989 to 1993 a pilot study on “digital optical archiving of medical records” was carried out at Heidelberg University Hospital. The study has shown the feasibility of digital optical archiving in hospitals if done under certain conditions. In 1995, Heidelberg University Hospital adopted a procedure for“ digital optical archiving of medical records”. The digital optical archive will first be filled with the medical records of the department of neurosurgery and the endoscopic and echographic images and reports of the department of internal medicine. It is to be expected that this procedure will gradually lead to an integrated functionality on health-care professional workstations, to a hospital-wide use of an electronic patient record, and to media-independent document management systems. The paper focusses on the potentials of digital optical archiving as an integral part of hospital information systems, and on the requirements for the systematic managements of hospital information systems with respect to digital optical archives.